Contemplative Correspondence and the Muscle of Metaphor: An Interview with Rev. Karen Hering - Christopher Basgier (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
Karen Hering, a Unitarian Universalist minister serving Unity Church-Unitarian in St. Paul, Minnesota, is author of Writing to Wake the Soul: Opening the Sacred Conversation Within. In her book, Rev. Hering leads readers through the practice of contemplative correspondence, which she describes as “a spiritual practice of writing rooted in theology and story; drawn to the surface by questions, prompts, and ellipses; and most fully experienced when its words are accepted as invitations into conversations and relationships with others” (xx). A committed Unitarian Universalist myself, I first learned about Rev. Hering and her book from my own minister, Rev. Chris Rothbauer, after I delivered a lay-led service at Auburn Unitarian Universalist Fellowship titled “Writing as a Way of Being Human,” inspired by Robert Yagelski’s Writing as a Way of Being. I bought her book and began working my way through it, writing from its myriad prompts on topics like love, grace, and redemption. I was nearly finished with it when I had opportunity to interview Rev. Hering about the ways writing can serve as a meaningful contemplative practice in our present moment. We spoke via Zoom on the eve of the 2020 presidential election, she in her garret office, me in my kitchen. Our conversation ranged far, from her experiences reading while bedridden during her childhood, to the power of metaphor for expanding our spiritual purview, to the ways embodied writing can counteract the detrimental effects of whiteness. We began our conversation with a traditional Unitarian Universalist ritual: a chalice lighting and a reading. The chalice itself symbolizes “the light of reason, the warmth of community, and the flame of hope” (“Flaming Chalice”).
Keywords: Correspondence; Metaphor; Karen Hering